Program Kemitraan Pelatihan Sertifikasi Halal Gratis (Sehati) Untuk UMKM di Kecamatan Kamang Magek Kabupaten Agam - Hendri Andi Mesta; Halkadri Fitra; Mike Triani; Miftahul Khair; Venny Irmi (Universitas Negeri Padang, 2023)
Kamang Magek District in Agam Regency has 177 small industries with 708 workers and 2 large industries with 51 workers. The products produced are dominated by the food sector so that product halalness is the main thing to pay attention to. Along with this, activities are needed regarding the need for the halalness of a product that will be consumed by the public for existing industrial players. Through the initiation of the Nagari government, Kamang Hilia sent a request to LPPM Padang State University to carry out community service activities regarding product halal certification. Community service activities are carried out by inviting resource persons from the Padang State University Halal Center in the form of training and discussions as well as assistance in the process of obtaining halal certification. This activity will succeed the Sehati program targeted by the government, especially for the province of West Sumatra. With this training, communication and supervision of industry players is getting better and opening opportunities for small partner industries to obtain a significant number of halal certificates.